Relationship between health literacy and generalized anxiety disorder during the COVID-19 pandemic in Khuzestan province, Iran - Dadgarinejad, Amirreza; Nazarihermoshi, Nargess; Hematichegeni, Negar; Jazaiery, Mahta; Yousefishad, Shabnam; Mohammadian, Hashem; Sayyah, Mehdi; Dastoorpoor, Maryam; Cheraghi, Maria (Frontiers in Psychology, 2024)
Pandemic of COVID-19, many changes occurred in various cultural, social, and economic fields, leading to the creation of psychological effects, especially anxiety, in the community. Fear and anxiety about emerging diseases (corona), less participation in preventive behaviors, reduces individual resistance and ultimately lowers the quality of life. Therefore, we aimed to investigate the relationship between health literacy and General anxiety disorders During COVID-19 Pandemic in Khuzestan province; Iran. Methods: It was a descriptive-analytical (cross-sectional) study conducted on among aged 18 -65 in Khuzestan province during the years 2020-2021 through online sampling. Due to the prevalence of coronavirus and the impossibility of face-to-face communication, the questionnaire was designed on the Porseline Survey website and the questionnaire link was provided to participants through WhatsApp and Telegram. The data collection tool includes the Iranian Health Literacy Questionnaire, which includes 33 items, and the Generalized Anxiety Disorder Scale, which has 7 items based on a Likert scale. Data analysis was performed using STATA14 software and descriptive and analytical statistical tests at a significant level less than 0.05 .The mean (standard deviation) score for health literacy was 52.9±9.3 and for generalized anxiety disorder was 5.2±3.1. A significant negative correlation was found between the mean of anxiety disorder and health literacy (p<0.05). The frequency of health literacy in individuals included 427 (37.8%) with inadequate health literacy, 628 (55.6%) with marginal health literacy, and 75 (6.6%) with sufficient health literacy. There was a statistically significant difference between the mean of generalized anxiety disorder among individuals with different levels of health literacy (p<0.05) .As the level of health literacy increases, the generalized anxiety disorder caused by fear of COVID-19 decreases. Therefore, increasing awareness and health literacy about this virus, its transmission, and prevention methods is very effective in managing anxiety and stress caused by the coronavirus. Paying attention to the issue of health literacy, generalized anxiety disorders, and taking preventive behaviors can be an effective tool for planners, health officials and policymakers to promote health literacy for any type of disease.